Pergulatan Perpanjangan Masa Jabatan Kepala Desa dalam Perpektif Hukum dan Demokrasi - Luhukay, Roni Sulistyanto (Jurnal Hukum Caraka Justitia, 2024)
The current village head's term is considered insufficient to develop the village due to tension and polarization after the village head election, and the village head's term of office is too short which will fail to achieve the vision and mission. In this research, the researcher used a normative legal research method, with this method it will be able to provide an overview of the problem of extending the term of office which has the potential to make the democratic climate unhealthy and can foster oligarchy in the village. Democracy is interpreted as an effort to limit power and build elite circulation as part of ending oligarchy and excessive accumulation of power. Extension of the village head's term of office is considered to injure the spirit of democracy itself considering that elite circulation does not occur briefly and accumulation carried out over a long period will foster dictatorial power.